A STUDY OF ISLAMIC EDUCATION IN RELATION TO THE EXEMPLARY VALUES OF THE PROPHET’S COMPANIONS IN THE BOOK STORIES FROM THE DESERT: COMPANIONS OF THE PROPHET BY DR NIZAR ABAZHAH - Sinta Amalia Sinta Amalia; Hidayatu Munawaroh; Nugroho Prasetya Adi (Jurnal Ikhtibar Nusantara, 2026)
Exemplary behavior is an important educational method in Islam because it plays a role in the formation of students' morals and character. One source of exemplary behavior that can be used as a reference in Islamic Religious Education is the stories of the Prophet's companions documented in various Islamic literature. This study aims to analyze the exemplary values ​​of the Prophet's companions contained in the book Stories from the Desert: Companions of the Prophet by Nizar Abazah and examine their relevance to Islamic Religious Education. This study uses a qualitative approach with a library research type. The primary data source of the study is the book Stories from the Desert: Companions of the Prophet, while secondary data sources are obtained from various books, journals, and relevant literature. Data were collected through documentation techniques and analyzed using content analysis. The results of the study indicate that there are six exemplary values ​​of the Prophet's companions in the book, namely siddiq (honesty), trustworthiness, patience, courage, responsibility, and simplicity. These values ​​have strong relevance to Islamic Religious Education because they can support the formation of students' morals and character. The values ​​of siddiq and amanah contribute to the formation of honest and trustworthy characters, the values ​​of patience and courage help develop steadfastness in facing challenges and upholding the truth, while the values ​​of responsibility and simplicity support the formation of discipline, humility, and moderation in living life. Thus, the book Stories from the Desert: Companions of the Prophet can be used as a learning resource that supports the achievement of the goals of Islamic Religious Education in forming students with noble morals and Islamic character.